Dissection of the Activity of Agricultural Fungicides against Clinical Aspergillus Isolates with and without Environmentally and Medically Induced Azole Resistance - Jørgensen, Karin Meinike (J Fungi (Basel), 2021)
Azole resistance is an emerging problem in patients with aspergillosis. The role of fungicides for resistance development and occurrence is not fully elucidated. EUCAST reference MICs of 17 fungicides (11 azoles and 6 others), five azole fungicide metabolites and four medical triazoles were examined against two reference and 28 clinical isolates of A. fumigatus, A. flavus and A. terreus with (n = 12) and without (n = 16) resistance mutations. Eight/11 azole fungicides were active against wild-type A. fumigatus, A. flavus and A. terreus, including four (metconazole, prothioconazole-desthio, prochloraz and imazalil) with low MIC(50) (≤2 mg/L) against all three species and epoxiconazole, propiconazole, tebuconazole and difenoconazole also against wild-type A. terreus. Mefentrifluconazole, azole metabolites and non-azole fungicides MICs were >16 mg/L against A. fumigatus although partial growth inhibition was found with mefentrifluconazole. Moreover, mefentrifluconazole and axozystrobin were active against wild-type A. terreus. Increased MICs (≥3 dilutions) were found for TR(34)/L98H, TR(34)((3))/L98H, TR(46)/Y121F/T289A and G432S compared to wild-type A. fumigatus for epoxiconazole, propiconazole, tebuconazole, difenoconazole, prochloraz, imazalil and metconazole (except G432S), and for prothioconazole-desthio against TR(46)/Y121F/T289A, specifically. Increased MICs were found in A. fumigatus harbouring G54R, M220K and M220R alterations for five, one and one azole fungicides, respectively, compared to MICs against wild-type A. fumigatus. Similarly, increased MICs wer found for A. terreus with G51A, M217I and Y491H alterations for five, six and two azole fungicides, respectively. Azole fungicides showed activity against wild-type A. fumigatus, A. terreus and A. flavus, but not against all mutant isolates, suggesting the environmental route of azole resistance may have a role for all three species.